1996
DOI: 10.1016/0304-3959(95)00096-8
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of injured and intact afferents to neuropathic pain in an experimental rat model

Abstract: This study was conducted to determine the contribution of peripheral inputs from injured and intact afferent fibers to behavioral signs of neuropathic pain, using a previously developed neuropathic rat model. Neuropathic injury was produced by tightly ligating the left L5 and L6 spinal nerves; this procedure induced rats to display neuropathic pain behaviors in the ipsilateral hindlimb. The behaviors included signs of mechanical and cold allodynia, as well as ongoing pain. Five days after neuropathic injury, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(119 citation statements)
references
References 44 publications
7
111
1
Order By: Relevance
“…The present study demonstrated that in the injured L5 DRG, most of the p-ERK-IR neurons and a subpopulation of p-p38-IR neurons were large in size and that the ERK and p38 inhibitors reversed the L5 SNL-induced mechanical allodynia. Furthermore, L5 dorsal rhizotomy prevented the development of mechanical allodynia, as reported previously (Yoon et al, 1996;Sukhotinsky et al, 2004). These observations support the possibility that large-diameter A-fibers mediate mechanical allodynia, whereas nociceptive C-fibers mediate thermal hyperalgesia Pan et al, 2003).…”
Section: Mapk Activation In the Injured L5 Drg Neurons And Mechanicalsupporting
confidence: 88%
“…The present study demonstrated that in the injured L5 DRG, most of the p-ERK-IR neurons and a subpopulation of p-p38-IR neurons were large in size and that the ERK and p38 inhibitors reversed the L5 SNL-induced mechanical allodynia. Furthermore, L5 dorsal rhizotomy prevented the development of mechanical allodynia, as reported previously (Yoon et al, 1996;Sukhotinsky et al, 2004). These observations support the possibility that large-diameter A-fibers mediate mechanical allodynia, whereas nociceptive C-fibers mediate thermal hyperalgesia Pan et al, 2003).…”
Section: Mapk Activation In the Injured L5 Drg Neurons And Mechanicalsupporting
confidence: 88%
“…Spontaneous foot-lifting duration was measured as the cumulative duration in seconds for which rats lifted their ipsilateral hindfoot accompanied often by aversive behavior (e.g., foot shaking/licking) over 5 min. Foot lifting associated with exploratory behavior, locomotion, body repositioning, and grooming was excluded (Yoon et al, 1996). This was repeated twice (10 min total time) with an interval of 5 min.…”
Section: Behavioral Testsmentioning
confidence: 99%
“…There is also evidence that these adjacent, uninjured afferents may contribute to the development and maintenance of neuropathic pain (Wu et al, 2001, Gold et al, 2003, Lee et al, 2003. One proposed mechanism is that Wallerian degeneration in mixed roots may result in the release of degenerative by-products and subsequent changes in the cellular and electrophysiological properties of the adjacent uninjured afferents, thereby resulting in pain (Yoon et al, 1996, Li et al, 2000. In the present model, for example, as the L6 fibers travel with L5 afferents to some degree in the sciatic nerve, it is possible that by-products of L6 efferent axonal degeneration may affect the functional properties of the L5 afferents (Wu et al, 2001).…”
Section: A Motor Lesion Can Induce Sensory Plasticity Beyond the Levementioning
confidence: 99%